1985
DOI: 10.1152/jappl.1985.59.3.1008
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of N2 volumes during N2 washout requires dynamic adjustment of delay time

Abstract: Measurement of respiratory gas composition by a mass spectrometer lags behind the measurement of gas flow. To obtain specific gas volumes (e.g., the N2 volume) by multiplication and integration of concentration and flow, one has to synchronize flow and concentration signals using the delay time (TD) of the gas analyzer. During the N2 washout, however, gas composition changes and causes alterations of TD. This leads to errors of up to 17 and 70% in the measurement of pulmonary volume and series dead space, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…Both signals are measured simultaneously, and no delay time correction is necessary. This is an important advantage, as several studies (6,20) have shown that when gas fractions are measured by sidestream sampling, there is a substantial delay between gas analysis signal and the mainstream gas flow measurement signal, mainly caused by the transport time of the sampled gas. Furthermore, flow measurement with a conventional pneumotachograph must be corrected for changes in gas viscosity during gas washout (21), requiring cumbersome calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Both signals are measured simultaneously, and no delay time correction is necessary. This is an important advantage, as several studies (6,20) have shown that when gas fractions are measured by sidestream sampling, there is a substantial delay between gas analysis signal and the mainstream gas flow measurement signal, mainly caused by the transport time of the sampled gas. Furthermore, flow measurement with a conventional pneumotachograph must be corrected for changes in gas viscosity during gas washout (21), requiring cumbersome calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively the cumulative expired nitrogen volume is obtained by integrating the product of expiratory flow and nitrogen concentration and summing these over subsequent breaths. This method is technically demanding: it requires very careful dynamic synchronisation of flow and concentration signals, and linearisation of the nitrogen meter [160]. With both procedures errors can arise due to elimination of nitrogen from tissues and body fluids.…”
Section: Multibreath Nitrogen Wash-out Methodsmentioning
confidence: 99%
“…To characterize the patient's respiratory system, accessible pulmonary gas volume (APV) was determined using the nitrogen washout technique. The details of the wash-out technique including synchronization of flow and concentration signals have been described previously [18,19].…”
Section: Methodsmentioning
confidence: 99%